Risk stratification and diagnostic evaluation of patients found to have microscopic hematuria by their primary care providers - Clemens An; Jake Jeong; Cedrick Chiu; Evan Gaston; Amanda Kennedy; Kevan Sternberg (Journal of General and Family Medicine)
Abstract Background Our goal was to identify, and risk stratify primary care patients with microscopic hematuria (MH), describe the diagnostic evaluations they received, and determine whether the evaluations were consistent with the recommendations of the 2020 AUA/SUFU microscopic hematuria guidelines. Methods A retrospective review of patients presenting to primary care clinics with a diagnosis of MH was performed. The patient risk category was determined based on the 2020 AUA/SUFU guidelines. Diagnostic strategies were recorded, and guideline concordance was determined. Descriptive statistics were generated to describe outcomes. Results A total of 368 patients had a diagnosis of MH; 267/368 (72.6%) patients had all pertinent data available for risk stratification. One‐hundred and fifty‐six (58.4) patients were high‐risk and 55 (35.3%) had a urologic visit. Forty‐one of the 55 (75%) were diagnostically evaluated of which 13 (31.7%) were in‐line with guideline recommendations. Eighty‐two (30.7%) patients were at intermediate risk of which 33 (40.2%) had a urology visit. Of these 33 intermediate‐risk patients, 27 (81.8%) were diagnostically evaluated, five (18.5%) of which were in‐line with guideline recommendations. Twenty‐nine patients were low risk of which 4 (13.8%) had a urology visit. Three of the four patients seen by urology (75%) were evaluated with imaging studies and none received a cystoscopy. Conclusion Almost 60% of the patients in our cohort were high‐risk according to the AUA/SUFU 2020 guidelines. Across all strata, the majority of patients lacked a urology visit and diagnostic evaluation consistent with guideline recommendations. Future efforts should ensure appropriate urologic referral and optimize initial diagnostic strategies for patients with MH.